The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/molecules27154690
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Fe-O2 Intermediates in Dioxygen Activation by Iron Porphyrin Complexes

Abstract: Dioxygen (O2) is an environmentally benign and abundant oxidant whose utilization is of great interest in the design of bioinspired synthetic catalytic oxidation systems to reduce energy consumption. However, it is unfortunate that utilization of O2 is a significant challenge because of the thermodynamic stability of O2 in its triplet ground state. Nevertheless, nature is able to overcome the spin state barrier using enzymes, which contain transition metals with unpaired d-electrons facilitating the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Metalloporphyrin complexes exhibit exceptional catalytic properties for various chemical transformations, including O-O bond heterolysis [1][2][3][4], H-H bond formation [5,6], O 2 adsorption [4,7,8], and catalytic oxidation [9][10][11][12] due to high activity, stability, clear molecular structure, and the ability to mimic the cytochrome enzyme [13,14]. Previous studies have shown that changing the meso-position substituents of metalloporphyrins to modulate their redox properties can alter metal ions' activities, stability, and selectivity in catalytic processes [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Metalloporphyrin complexes exhibit exceptional catalytic properties for various chemical transformations, including O-O bond heterolysis [1][2][3][4], H-H bond formation [5,6], O 2 adsorption [4,7,8], and catalytic oxidation [9][10][11][12] due to high activity, stability, clear molecular structure, and the ability to mimic the cytochrome enzyme [13,14]. Previous studies have shown that changing the meso-position substituents of metalloporphyrins to modulate their redox properties can alter metal ions' activities, stability, and selectivity in catalytic processes [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, because natural enzymes cannot be extracted, their application in industrial production is also limited. Porphyrins consist of four pyrrole methylene α-carbon atoms connected to each other by a methylene bridge (=CH-) [ 15 ]. There are two pyrrole protons (N-H) in the porphyrin ring.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their high cost, highly restricted catalytic conditions and fragile nature, the practical applications of enzymes have been hindered. To overcome these problems of enzymes for practical applications, biomimetic systems have subsequently emerged as an effective approach to synthesize highly efficient biomimetic catalysts via mimicking certain key features of enzymes [31,32].…”
Section: Introductionmentioning
confidence: 99%